2001
DOI: 10.1053/jhep.2001.24749
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hepatitis C virus NS5A natural mutants in a hepatocytic cell line inhibits the antiviral effect of interferon in a PKR-independent manner

Abstract: The impact of hepatitis C virus NS5A protein mutations on interferon alfa (IFN-␣) signaling pathway, cell proliferation, and viability is an important issue that is still under debate. We have therefore combined transient and stable expression in a human hepatocytic cell line (Huh7) of 3 full-length NS5A sequences, isolated from patients with or without response to IFN-␣ therapy. Expression of all 3 NS5A-reduced IFN-␣ global antiviral activity on both vesicular stomatitis virus (VSV) and encephalomyocarditis v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 37 publications
3
49
0
1
Order By: Relevance
“…Some studies have suggested that NS5A may bind PKR and inhibits its activity (Gale et al, 1998). We recently reported, however, that at least in Huh7 cells, we did not show such an interaction (Podevin et al, 2001). These very important results turned to advantage, providing additional evidence for the speci®city of our present observations on HCV core.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Some studies have suggested that NS5A may bind PKR and inhibits its activity (Gale et al, 1998). We recently reported, however, that at least in Huh7 cells, we did not show such an interaction (Podevin et al, 2001). These very important results turned to advantage, providing additional evidence for the speci®city of our present observations on HCV core.…”
Section: Resultssupporting
confidence: 75%
“…HCV polyprotein expression impairs interferon-dependent signal transduction and in particular STAT DNA binding e cacy (Gale et al, 1998;Heim et al, 1999;Polyak et al, 1999). Furthermore, it has been proposed that two HCV proteins: E2 and NS5A, may bind PKR, inhibit its antiviral and anti-apoptotic activities and thus favor HCV chronicity and liver cell clone expansion (Gale et al, 1998;Taylor et al, 1999); the results concerning NS5A may di er depending on the cell line examined and we were unable to show such an association in HuH7 cells (Podevin et al, 2001). Nevertheless, the present results allow us to propose an alternative, and in fact contrasting mechanism for HCV core protein.…”
Section: Discussionmentioning
confidence: 61%
“…Recently, PODEVIN et al 28 have extended the discussion about the role of NS5A, questioning previous models that did not analyze the role of NS5A in hepatocytes and whose results should therefore be considered with caution. In their study, the first one on hepatocytes, the authors analyzed human hepatocytic cell lines (Huh 7) expressing NS5A sequences derived from one responder and two non-responders in the presence of interferon-alpha and exposed to virus strains sensitive to the drug.…”
Section: Viral Dynamics the Understanding Of Hcv Kinetics Is Fundamementioning
confidence: 99%
“…Recently, it was suggested that NS5A protein may also inhibit the antiviral effect of IFN in a PKR-independent manner in a human hepatocytic cell line [25] . Furthermore, a n o t h e r d o m a i n i n t h e N S 5 A r e g i o n , n a m e d V 3 (NS5A2356-2379) [26] , could also be linked to IFN resistance.…”
Section: Introductionmentioning
confidence: 99%